Peningkatan Proses Bisnis Menggunakan Business Process Improvement (BPI) Di Solo Bakery (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Solo Bakery is an UMKM (Usaha Mikro, Kecil dan Menengah) company that produces bread in Solo city. To maintain business and compete, short, effective and efficient business processes are needed so that they can support production. The business process of procurement (purchasing) of goods and payroll is required to be evaluated and modeled for a new business process (To-be). Evaluation using the Failure Model and Effect Analysis method and business process improvement plans with the streamlining tool from the Business Process Improvement method simulated with the Bizagi Modeler software obtained an average time saving for the goods procurement (purchasing) business process of 1 hour 14 minutes 38 seconds (24%) and the average payroll processing business time is 3 hours 48 minutes 13 seconds (35%). Keywords: Business Process, Failure Model and Effect Analysis, Streamlining, Simulation, Bizagi Modeler.